“НЕОПАТРИМОНИАЛ” ОНОЛЫН ОЙЛГОЛТЫГ ТАЙЛБАРЛАХ НЬ - Б.Эрдэнэдалай; Г.Мөнхтуяа (Politology, 2023)
The transition between a traditional state and a modern state has crucial impacts on economic and political development. During this transition, the transition state is preserved, which is called a neopatrimonial state. Generally, neopatrimonial state makes irrational decisions based on personal or group interests rather than making policies and decisions for the public interests. Since 1970, neopatrimonial theory was studied in the field of research. The theory's reasoning and how it explains political and social events are mainly discussed.